From female computers to male comput♂rs: Or why there are so few women writing algorithms and developing software. (August 2021) - Tassabehji, Rana; Harding, Nancy; Lee, Hugh; Dominguez-Pery, Carine
Software development is one of the few professions in Europe and the USA from which women are disappearing. Current explanations range from unproven assumptions that women cannot write algorithms to insights into the misogynistic culture of this profession. This article argues these explanations are inadequate, and illuminates how forms of masculinity constituted within software development put women in the ambivalent position of being either female or a coder, but not both. Using a poststructural theoretical position to analyse materials from a qualitative, interview-based study, we identified three constitutive ontologies of the person circulating within the profession. The Comput♂r is presumptively male and can merge with the machine, although a subset, Geeks, cannot demerge from it. The Human, presumptively female, can communicate with people but not the machine. The Ideal developer claims the best of both, that is, adept at writing algorithms and communicating with people. These ontologies are informed by a theory of the body circulating within software development whose norms are unattainable by women. Female bodies are envisaged as 'flesh', and male bodies as a futuristic merger of body and machine. This Janus-faced theory excludes female developers from practising their profession.